2010
DOI: 10.1016/j.mambio.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of shape variation in the eastern African gerbils of the genus Gerbilliscus (Rodentia, Muridae): Environmental correlations and implication for taxonomy and systematics

Abstract: Gerbilliscus has been in recent years the subject of new molecular and karyological investigations that shed new light on the evolutionary processes of this taxon. However, the patterns of phenotypic diversification of Gerbilliscus remain poorly understood. Furthermore, the molecular phylogenetic analyses posed new questions concerning the systematics and taxonomy of the whole genus and revealed the possible occurrence of cryptic species and hence the need to carry out a taxonomic revision. We used geometric m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
0
17
1
Order By: Relevance
“…Furthermore, TPS deformation grids from extreme PLS-1 environmental values showed no obvious patterns in these differences ( Figure 5), indicating that they were not concentrated in functionally important cranial regions. This result is unlike that of other similar gerbil studies, which show stronger cranial climatic adaptation patterns, in regions that include the tympanic bulla, palate, and teeth (Alhajeri, 2014(Alhajeri, , 2018Colangelo et al, 2010;Tabatabaei Yazdi, Colangelo, & Adriaens, 2014).…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Furthermore, TPS deformation grids from extreme PLS-1 environmental values showed no obvious patterns in these differences ( Figure 5), indicating that they were not concentrated in functionally important cranial regions. This result is unlike that of other similar gerbil studies, which show stronger cranial climatic adaptation patterns, in regions that include the tympanic bulla, palate, and teeth (Alhajeri, 2014(Alhajeri, , 2018Colangelo et al, 2010;Tabatabaei Yazdi, Colangelo, & Adriaens, 2014).…”
Section: Discussioncontrasting
confidence: 98%
“…Intraspecific morphological variation in rodents (and gerbils in particular) is increasingly being assessed using geometric morphometrics—an approach that allows for the examination of shape and size variation independently (see Zelditch, Swiderski, Sheets, & Fink, ). For example, Colangelo, Castiglia, Franchini, and Solano () investigated the association between cranial variation with environmental variability in four species of Gerbilliscus Thomas,1897—they found that cranial shape variation was correlated with climatic variables, which they interpreted in terms of adaptation to “different trophic resources.” Tabatabaei Yazdi, Adriaens, and Darvish () examined the association between cranial variation with geography in Meriones meridianus Pallas, 1773, and found evidence that populations exhibited geographic disparity in both cranial size and shape, the latter includes differences in the morphology of the bulla, nasals, molars, and the incisive foramen. Similarly, Tabatabaei Yazdi, Adriaens, and Darvish () examined the association between cranial variation with both environmental and geographical variability in Meriones crassus Sundevall, 1842.…”
Section: Introductionmentioning
confidence: 99%
“…) and their morphological variation (Colangelo et al. ). In these studies, Colangelo and colleagues recognized three major clades within Gerbilliscus that correspond to major geographic subdivisions, and supported the synonymy of the Gerbillurus and Gerbilliscus (Colangelo et al.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in tympanic bulla size can be considered to be adaptive (Lay 1972;Webster & Webster 1984;Van der Straeten & Dieterlen 1992;Webster & Plassmann 1992;Huang et al 2002), as it causes an increased amplification of sound that allows rodents to increase low-frequency hearing and detect an approaching predator more rapidly (Burda et al 1990;Mason 2001Mason , 2003Huang et al 2002;Schleich & Vasallo 2003). As such, a bulla hypertrophy may reflect a morphological adaptation for efficient vocal communication in a desert environment, where rodent population densities are low, and in an underground environment as well (Petter 1961;Harrison 1972;Lay 1972;Darvish 2009;Colangelo et al 2010). This is corroborated by Vaughan et al (2000) and our study, as smaller tympanic bullae were found in populations occurring in regions with higher levels of rainfall (and vice versa).…”
Section: Geoclimatic Correlation Of the Morphological Variationmentioning
confidence: 99%